Pengaruh Pendidikan dan Pelatihan, Motivasi, serta Budaya Organisasi terhadap Kinerja Pegawai Distrik Navigasi Kelas I Palembang - Deni, Muhammad (Jurnal Ilmu Manajemen, 2014)
The purpose of this study was to determine the influence of Education and Training, Motivation And Organizational Culture To Employee Performance of District of Navigation Office Class I Palembang. Population of this studyas many as 80 employees. The results of calculations using SPSS, showed that: R2 of 0.374 (37.4% ), illustrates that the performance of employees (Y), can be explained by all independent variables 37.4%, while the remaining62.4%, can be explained by other factors, which are not included in this study. From the result of hypothesis F test , obtained value of Fcompute (15.108 ) > Ftable (2.725), means that there is the influence of education andtraining, motivation and organizational culture together to employee performance. While the results of the hypothesis t test, there are influences of education and training then motivation to performance, but there is no influence of organizational culture on performance.